Efektivitas Kinerja Penanganan Tindak Pidana Narkoba Anak Di Bawah Umur Pada Kepolisian Resort Kabupaten Pinrang - Yuliana, Yuliana; Parawangi, Anwar; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aims to determine the effectiveness of the performance of child drug crime handling at the Pinrang District Police. This type of research is a descriptive study with a qualitative approach. The number of informants in this study were 6 people. The data used are primary data and secondary data. The results showed that the investigation process of narcotics abuse by children certainly experienced various kinds of obstacles. In various cases including narcotics crimes against children, the investigator seems to have a dual role, apart from being hampered by various obstacles. Investigators must also provide solutions or outreach to the public. Such as: it consumes time compared to investigations in adult cases, the investigator hopes that the parties involved in assisting the investigation process are expected to cooperate cooperatively, the lack of public awareness to report so that the police are expected to provide information to the community about narcotics crime, the lack of the role of the family environment , as parents should be more active in maintaining their children by following developments. Keywords: Kinejra Effectiveness, Underage Children